(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2025)
Pediatric scalp injuries caused by agricultural machinery are rare but potentially devastating with long-term implications on craniofacial growth and psychosocial development. These injuries present unique reconstructive challenges due to the scalp’s limited elasticity, robust vascularity and the need to preserve both function and cosmesis in a developing child. This report describes the staged surgical management of a 1.5-year-old boy who sustained extensive scalp lacerations and calvarial fractures following entrapment of scalp hair in a rice-cutting machine. Initial wound closure was followed by partial flap necrosis. Then a secondary procedure involving transposition flap reconstruction and split-thickness skin grafting (STSG) was performed. This case underscores the importance of a systematic, adaptive reconstructive strategy, adherence to the principles of the reconstructive ladder and long-term multidisciplinary follow-up. Psychological support, parental counseling and vigilance for late sequelae were integral components of care. Journal of Paediatric Surgeons of Bangladesh (2021) Vol. 12 (1 & 2): 41-44